2005
DOI: 10.1080/10284150500445795
|View full text |Cite
|
Sign up to set email alerts
|

Mixture of essential fatty acids lowers test anxiety

Abstract: Test anxiety is an incapacitating academic syndrome. This study shows that administration of a polyunsaturated fatty acid mixture of omega-3 and -6 can improve the behavioral variables associated with this type of anxiety, i.e. appetite, mood, mental concentration, fatigue, academic organization and poor sleep, as well as lowering elevated cortisol level, with a corresponding reduction of anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 12 publications
3
75
0
Order By: Relevance
“…Of these studies, Behan et al (120) found decreases in fatigue following supplementation with EPA þ DHA compared with placebo in sixty-three individuals diagnosed with chronic fatigue syndrome, Fontani et al (118) found decreases following supplementation with EPA þ DHA compared with placebo in thirty-three healthy volunteers, and Yehuda et al (144) found decreases in fatigue following supplementation with ALA þ n-6PUFA compared with placebo in 126 individuals suffering from test anxiety. Benefits of n-3PUFA supplementation for individuals with chronic fatigue syndrome have also been reported in several individual cases (147) .…”
Section: Trial Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…Of these studies, Behan et al (120) found decreases in fatigue following supplementation with EPA þ DHA compared with placebo in sixty-three individuals diagnosed with chronic fatigue syndrome, Fontani et al (118) found decreases following supplementation with EPA þ DHA compared with placebo in thirty-three healthy volunteers, and Yehuda et al (144) found decreases in fatigue following supplementation with ALA þ n-6PUFA compared with placebo in 126 individuals suffering from test anxiety. Benefits of n-3PUFA supplementation for individuals with chronic fatigue syndrome have also been reported in several individual cases (147) .…”
Section: Trial Evidencementioning
confidence: 99%
“…Ness et al (117) measured anxiety following advice to eat fish or supplementation with EPA in a large sample (n 452) of angina sufferers, Fontani et al (118) measured anxiety following supplementation with EPA þ DHA þ other n-3PUFA in thirty-three healthy volunteers, Rogers et al (119) measured anxiety following supplementation with EPA þ DHA in 218 individuals with mild -moderate depressed mood, Fux et al (125) studied anxiety and obsessive-compulsive behaviour following E-EPA in eleven individuals diagnosed with obsessive-compulsive disorder, and Yehuda et al (144) studied mood and organisational abilities following supplementation with ALA in a group of 126 test anxiety sufferers. Improvements following treatment compared with placebo were found in two studies (118,144) , but no benefits of treatment compared with placebo were found in the other three studies (117,119,125) .…”
Section: Trial Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Many secondary plantmetabolites have been reported to possess lipid-lowering properties (Sharma, S.B., et al, 2003;Yehuda, et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In a 2013 study (Yehuda, Rabinovitz & Mostofsky, 2013), a correlation was demonstrated between the consumption of essential fatty acids and a reduction in test anxiety. The use of biofeedback in Bradley's et al (2010) study noted a correlation between biofeedback participants and reduced test anxiety.…”
Section: Interventionsmentioning
confidence: 99%